The Implementation of Mandatory Audit Firm Rotation as tool to enhance Audit Reform in South Africa: A Case of KwaZulu-Natal - AMINU, Munkaila; NOMLALA, Bomi Cyril; BALDAVOO, Kiran; MVUNABANDI, Jean Damascene (PT Keberlanjutan Strategis Indonesia, 2023)
Using a quantitative research method, this article examined the perceptions of audit experts concerning the influence of mandatory audit firm rotation on audit reform (AR) in the province of KwaZulu-Natal. Data was gathered from 102 audit experts knowledgeable in the field of accounting and auditing from Tier 2 audit firms and two public institutions and used for data analysis. The empirical results of this study were two-fold. Firstly, the descriptive statistics provided a general overview of the respondents’ opinions. The majority of respondents agreed that MAFR implementation would strengthen audit reform, thereby validating the initial position of the Independent Regulatory Board of Auditors. In addition, most participants agreed that the ramification of the imposition of additional costs could not be ignored. Moreover, the utilization of SPSS on ordinal logistic regression also found that the probability of a decrease in the progress of audit reforms is significantly higher when mandatory audit firm rotation is in place, and a non-significant positive predictor of mandatory audit firm rotation would increase audit independence. This article contributes to existing knowledge and the continuous discourse on mandatory audit firm rotation rule in South Africa. Conclusively, the study, therefore, recommends that since the research was limited to Kwazulu-Natal, future studies should broadly include registered auditors and academics from institutions and firms in different South African provinces to obtain diverse views about pre-and post-implementation of the rule in 2023 to compare the effects of the policy on audit independence.